NUFFT-based imaging of vegetation on graphic cards - Capozzoli, A.; Curcio, C.; D’Elia, G.; Di Vico, A.; Liseno, A.; Vinetti, P. (Видавництво Національного університету "Львівська політехніка", 2009)
We present an algorithm for the fast tomography of vegetation, based on a Radon mathematical setting and on the combined use of advanced processing algorithms (Non-Uniform FFTs) and hardware resources (Graphic Processing Units - GPUs). The algorithm performance is firstly numerically estimated, showing the favorable trade off between faithfulness and speed, and highlighting the convenience of the GPU implementation against that on CPU. Experimental results on anechoic chamber data complete the algorithm assessment.
Keywords: tomography; Imaging; NUFFT; GPU; vegetation; Fast Backprojection